Specific PCR assay for a tannin-tolerant Selenomonas ruminantium isolate, derived from helicase coding sequences - Bishop, Richard P.; Obura, M.; Odongo, D.; Odenyo, A.A. (American Society for Microbiology, 2004)
Sequences from a tannin-tolerant Selenomonas ruminantium isolate (EAT2) that hydrolyzes gallic acid were identified. Two exhibited identity to helicases with a wide phylogenetic distribution. PCR amplification by using primers from one helicase gene detected 2,000 to 5,000 EAT2 genome equivalents but did not amplify total gastrointestinal microbial DNA of nine other ungulate species.